Bio‐PUF‐MAC authenticated encryption for iris biometrics. (27th May 2020) - Narasimhan, Sivasankari; Arunachalam, Muthukumar
Abstract: Biometrics is one of the ways for human authentication. Fabrication of biometrics by intruders, limits the accuracy of authentication. The user‐specific keys (ie, ) pseudo‐random numbers give more security for biometric template protection and increase the accuracy of authentication also. The user‐specific token or keys can also be fabricated by intruders by any of the prediction methods. To avoid the creation of fake biometric and fake user‐specific keys, a device‐specific Physical Unclonable Function (PUF) is proposed. In this article, iris authentication is provided by unclonable PUF‐based true random numbers to enhance the unique authentication. Nonreversible Message Authentication Codes (MAC) are developed using PUF and Discrete Wavelet Transform features of iris biometrics. Systematically, MAC codes also created with, encryption algorithm. Encryption is additionally providing confidentiality in the individual iris. Experiments are done with CUHK Iris Image Dataset. Proposed Bio‐PUF system has significant functional advantages in point of view of the unclonable pseudo‐random number from PUF. Experimentally, Avalanche effect, entropy, NCPR, and UACI parameters are analyzed with PUF‐based crypt functions. For 75% of matching with the Bio‐PUF‐MAC codes with enrolment, the accuracy for correct identification is 77.73%.